A case of high-output heart failure caused by a femoral arteriovenous fistula after endovenous laser ablation treatment of the saphenous vein. (May 2015) - Hashimoto, Osamu; Miyazaki, Takuya; Hosokawa, Joji; Shimura, Yumi; Okuyama, Hiroshi; Endo, Masahiro
Endovenous laser ablation treatment has become the less invasive therapeutic choice for the treatment of superficial venous insufficiency and varicose veins. A 64-year-old woman presented at our hospital with varicose veins and prior endovenous laser ablation treatment. The patient had high-output heart failure caused by a right femoral arteriovenous fistula. She was treated medically and underwent an open repair of the right superficial femoral artery and the right femoral vein with complete resolution of the arteriovenous fistula and heart failure. Here, we have reviewed the literature and discussed possible causes of the complication of arteriovenous fistula after endovenous laser ablation treatment.